Monogenoids (Polyonchoinea, Dactylogyridae) from Hydrolycus armatus (Characiformes, Cynodontidae) with the description of a new species of Rhinoxenus and the proposal of a new genus from the Xingu River, Pará, Brazil - Soares, Geusivam B.; Magalhães, Keila X.; Silva, Ana Carolina; Carneiro, Jânio S.; Barbosa, Lucineia L.; Costa, Nayna G. S.; Domingues, Marcus V. (Zootaxa, 2019)
One new species of Rhinoxenus Kritsky, Boeger & Thatcher, 1988 from the nasal cavities and four new species of Mymarothecioides n. gen. from the gills are described in Hydrolycus armatus (Jardine & Schomburgk). They were collected in the Xingu River, Pará, Brazil. Rhinoxenus cachorra n. sp. is characterized by having a ventral anchor with inconspicuous roots, and point with fish-hook-like termination; copulatory complex comprising a spiraled male copulatory organ (MCO) with two counterclockwise coils, and an accessory piece with an expanded, bifurcated distal portion. Mymarothecioides n. gen. is proposed and characterized for species without eyes, with or without accessory chromatic granules; copulatory complex comprising articulated MCO, accessory piece; MCO a broad arcuate tube; an accessory piece with a hooked termination in the distal portion; a dextro or midventral non-sclerotized vagina; an anteromedial projection on the ventral bar. Mymarothecium whittingtoni Kritsky, Boeger & Jégu, 1996 is transferred to Mymarothecioides n. gen. as Mymarothecioides whittingtoni (Kritsky, Boeger & Jégu, 1996) n. comb.